Global Demands – Local Practices: Working towards Inclusion of Gender Equality in Teacher Education in Finland and Sweden - Kreitz-Sandberg, Susanne; Lahelma, Elina (Nordic Journal of Comparative and International Education (NJCIE), 2021)
Gender equality is a global aim that has been presented in numerous documents. However, teacher education programs in many countries still lack sustainable strategies for working towards gender equality in education. Working successfully in this area may promote more sustainable practices in schools to reach gender-fair societies. The Nordic countries are known for pro-active gender policies and they provide interesting cases for investigating achievements and struggles in the field. The purpose of this article is, from an international comparative perspective, to explore the rationales and practices when working with issues of gender equality in Finnish and Swedish teacher education and to reflect on related concepts. We describe, analyse and compare local practices, theoretical frameworks and challenges by revisiting gender and teacher education research and equality projects from the 1980s up to today. The comparative methodology chosen facilitates understanding examples from two neighbouring countries, illustrating different ways to develop policies and strategies. Local actors not only follow global claims to work with gender and equality in teacher education but also play an active role and contribute to these discourses. Our study suggests that gender equality cannot be achieved overnight; appropriate strategies need to be negotiated constantly in specific national and institutional contexts at universities and teacher education institutions.